Spinal muscular atrophy: descriptive analysis of a case series. - Pires, Mafalda; Marreiros, Humberto; Francisco, Rita Cardoso; Soudo, Ana; Vieira, José Pedro (Acta Médica Portuguesa, 2011)
Spinal Muscular atrophy (SMA) is a genetically determined specific neuromuscular disease, characterized by the deterioration of spinal a motor neurons, causing progressive muscular atrophy and weakening. It is genetically determined, with the absence or mutation of the survival motor neuron 1 (SMN1) as a hallmark. A similar copy of the SMN1, named SMN2, modulates the severity of the disease. Several types of the disease have been described along with several classification systems based either on the age at onset of symptoms or on the maximum function achieved. SMA leads to a vast group of secondary manifestations in various organ systems, particularly the respiratory, muscle-skeletal and gastrointestinal.To study the population with the diagnosis of SMA (clinical and/or genetic) followed in the Physical Medicine and Rehabilitation outpatient clinic (PMR) of the Hospital de Dona Estefânia (HDE) in Lisbon, from January 2007 to October 2009.The authors conducted a retrospective study focusing on socio-demographic, clinical parameters, evolution and complications of the disease.Twelve children were enrolled in the study, with age ranging from 0 months to 21 years, four diagnosed with SMA type III, seven with SMA type I and one with SMA II. An inverse relation was found between the severity of the course of illness and the age at onset and maximum motor function achieved. All patients sustained recurrent lower respiratory infections during the course of the disease. Respiratory insufficiency complicated by cardio-respiratory arrest was the cause of death in the deceased patients. The main musculoskeletal complication was the development of contractures in the main joints of the lower limbs, as well as scoliosis. Dysphagia was the main gastroenterological complication.The authors conclude that the lack of acquisition of motor developmental milestones is correlated to worse vital and functional prognosis.